Ingestion, Immunity, and Infection: Nutrition and Viral Respiratory Tract Infections - Govers, Coen; Calder, Philip C.; Savelkoul, Huub F. J.; Albers, Ruud; van Neerven, R. J. Joost (Frontiers in Immunology, 2022)
Respiratory infections place a heavy burden on the health care system, particularly in the winter months. Individuals with a vulnerable immune system, such as very young children and the elderly, and those with an immune deficiency, are at increased risk of contracting a respiratory infection. Most respiratory infections are relatively mild and affect the upper respiratory tract only, but other infections can be more serious. These can lead to pneumonia and be life-threatening in vulnerable groups. Rather than focus entirely on treating the symptoms of infectious disease, optimizing immune responsiveness to these infections may help steer towards a more favorable outcome. Nutrition may have a role in such prevention through different immune supporting mechanisms. Nutrition contributes to the normal functioning of the immune system, with various nutrients acting as energy sources and building blocks during the immune response. Many micronutrients (vitamins and minerals) act as regulators of molecular responses of immune cells to infection. It is well described that chronic undernutrition as well as specific micronutrient deficiencies impair many aspects of the immune response and make individuals more susceptible to infectious diseases, especially in the respiratory and gastrointestinal tracts. In addition, other dietary components such as proteins, pre-, pro- and synbiotics, and also animal- and plant-derived bioactive components can further support the immune system. Both the innate and adaptive defense systems contribute to active antiviral respiratory tract immunity. The initial response to viral airway infections is through recognition by the innate immune system of viral components leading to activation of adaptive immune cells in the form of cytotoxic T cells, the production of neutralizing antibodies and the induction of memory T and B cell responses. The aim of this review is to describe the effects of a range different dietary components on anti-infective innate as well as adaptive immune responses and to propose mechanisms by which they may interact with the immune system in the respiratory tract.